2014
DOI: 10.5027/andgeov41n1-a03
|View full text |Cite
|
Sign up to set email alerts
|

Geocronología U-Pb e isótopos de Hf-O en circones del batolito de la Costa Pensilvaniana, Chile.

Abstract: ABSTRACT. The Coastal Batholith of south-central Chile between latitudes 33° and 40°S is composed of calc-alkaline granitoids emplaced in a relatively restricted time period. New SHRIMP U-Pb zircon ages on eight quartzdioritic to granitic rocks collected over a distance of 800 km yielded ages between 300 and 320 Ma, Pennsylvanian (late Carboniferous). Lu-Hf isotopic analyses on the same zircon grains have initial εHf (i) values from +1.67 to -5.64. The δ 18 O ratios for that grains range from 6.4 to 8.6‰. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 32 publications
(33 reference statements)
1
12
0
1
Order By: Relevance
“…We prefer the concept of Chaitenia as an (initially) offshore Devonian island arc as suggested in Hervé et al, (2016) as the colliding body. A post-470 Ma depositional age for the majority of these samples is established by the U-Pb data for detrital zircons, but in some cases a mid-Paleozoic age is confirmed by the fact that they are intruded by igneous rocks dated at 306±2 Ma (Cuesta de Rahue), penecontemporaneous with the Pennsylvanian Coastal Batholith of Chile (Deckart et al, 2014), and of the Devonian age in the granitic body intruding the rocks of the Llanquihue metamorphic complex (McDonough et al, written communication, 2001) at the ENAP borehole Rahue-2.…”
Section: Devonian Zircon Agesmentioning
confidence: 91%
“…We prefer the concept of Chaitenia as an (initially) offshore Devonian island arc as suggested in Hervé et al, (2016) as the colliding body. A post-470 Ma depositional age for the majority of these samples is established by the U-Pb data for detrital zircons, but in some cases a mid-Paleozoic age is confirmed by the fact that they are intruded by igneous rocks dated at 306±2 Ma (Cuesta de Rahue), penecontemporaneous with the Pennsylvanian Coastal Batholith of Chile (Deckart et al, 2014), and of the Devonian age in the granitic body intruding the rocks of the Llanquihue metamorphic complex (McDonough et al, written communication, 2001) at the ENAP borehole Rahue-2.…”
Section: Devonian Zircon Agesmentioning
confidence: 91%
“…Furthermore, zircons of late Carboniferous age have been reported in Paleozoic units of the Coastal Cordillera of central Chile (ca. 300-320 Ma, U-Pb, Deckart et al, 2014), but they seem to be too far away to explain their influence in the Alto Tunuyán Basin.…”
Section: Other Unclear Sourcesmentioning
confidence: 99%
“…Sediments of late Paleozoic age have also been identified in red clastic sequences of Kimmeridgian/Tithonian age in northern Chile, and their likely sources attributed to numerous Carboniferous to Permian intrusions that crop out in the Principal Cordillera (28-29°S; Oliveros et al, 2012). At the latitude of the present study, no Paleozoic plutonic rocks older than 320 Ma have been reported in the Chilean territory (Deckart et al, 2014). Given the large size of the granitic clasts, their source must have been an unexposed extension of Carboniferous granitoid located near the Chile-Argentina border, rather than the presentday nearest outcrops of Paleozoic granitoids in the Coastal Cordillera between 33° and 38°S.…”
Section: Age and Provenance Of The Río Damas-tordillomentioning
confidence: 82%